Peran KH. Imam Zarkasyi dalam Pembaharuan Pendidikan Pesantren di Indonesia - Nuruddin, Nuruddin; Tarno, Tarno; Amiruddin, Fadjar; Khoir, Mulyanto Abdullah (TSAQOFAH, 2025)
KH. Imam Zarkasyi is a central figure in the modernization of Islamic boarding school (pesantren) education in Indonesia. Through the establishment of Pondok Modern Gontor, he successfully formulated a progressive and responsive Islamic education system attuned to contemporary developments. This article aims to examine his role and reformist ideas within the pesantren education system, focusing on curriculum, institutional management, and pedagogical approaches. A qualitative method with a historical and descriptive-analytical approach was employed. The findings reveal that KH. Imam Zarkasyi developed an integrative pesantren education model that combines Islamic values with modern scientific knowledge, while also emphasizing character building and student independence. His educational innovations include the implementation of a classical classroom system, instruction in foreign languages (Arabic and English), and a balanced orientation between religious (ukhrawi) and worldly (duniawi) dimensions. This model has positioned Gontor as a prototype of the modern pesantren, capable of producing intellectual leaders and religious scholars. The study indicates that KH. Imam Zarkasyi’s reformist approach remains highly relevant as a strategic reference for improving the quality of pesantren education in the era of globalization.